Financial Management Strategy for Sustainable Development of Micro, Small, and Medium Enterprises (MSMEs): Evidence from Pondok Petir Subdistrict, Bojongsari District, Depok City - Ahmad Fadli; Ramadani Pardian; Ika Agustina; Rila Janara Putri; Dinda Olivia Silva (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to formulate a sustainable financial management strategy for Micro, Small, and Medium Enterprises (MSMEs) located in Pondok Petir Subdistrict, Bojongsari District, Depok City. While MSMEs constitute a vital engine of the national economy, practitioners in this sector continue to grapple with persistent structural constraints including limited financial literacy, restricted access to formal financing, and vulnerability to production cost volatility. A descriptive qualitative research design was adopted, employing purposive sampling to engage 92 MSME operators as primary informants, complemented by field observations, questionnaire surveys, and in-depth interviews. To enhance analytical depth and validate preliminary findings, a Focus Group Discussion (FGD) was conducted with a diverse group of stakeholders encompassing representatives from the local government, MSME associations, business development clinics, academic institutions, and commercial banking entities. The findings reveal that MSMEs in Pondok Petir possess notable organizational strengths, including a sizeable and cohesive business community, demonstrated entrepreneurial resilience, and locally competitive advantages in the culinary and creative service industries. Nonetheless, critical weaknesses persist in the form of inadequate financial literacy, absence of standardized bookkeeping, and constrained capital access. On the external dimension, significant opportunities arise from government-driven development programs, the availability of microfinance instruments, and expanding digital marketing ecosystems, while threats emanate from raw material price instability, fluctuating consumer demand, and market saturation. SWOT matrix analysis positions MSMEs in Quadrant I, prescribing an aggressive SO strategy characterized by measures to bolster financial literacy, formalize cooperative-based financing mechanisms, accelerate digital marketing adoption, and establish collective procurement systems for raw materials. This research contributes to the development of a participatory financial strategy framework aimed at reinforcing the competitive capacity of local MSMEs and may serve as a strategic reference for governments, financial institutions, academics, and the broader business community